Authorship and Participation in the Context of Organized Criminality - Viana, Lurizam Costa (2015)
This paper has the scope of studying the institutions of authorship and participation in the context of criminal organizations. It intends to analyze the criteria for assigning members of an organized criminal group as authors or participants, regarding their penal liability. Firstly, general aspects of authorship and participation are analyzed. Then, it is established the relationship between the various types of structures of criminal organizations, the division of labor identified among their members and the allocation of their conducts. In this sense, it is approached the theory of "domain by organization", formulated by Claus Roxin as an independent type of mediate authorship in the cases of domain of the fact by the "domain of an organized apparatus of power". Finally, the implications of Law 12.850/13 are identified, in the matter of authorship and participation in a criminal organization.